Contribution of the PhoP-PhoQ and PmrA-PmrB Two-Component Regulatory Systems to Mg(2+)-Induced Gene Regulation in Pseudomonas aeruginosa - McPhee, Joseph B. (American Society for Microbiology, 2006)
When grown in divalent cation-limited medium, Pseudomonas aeruginosa becomes resistant to cationic antimicrobial peptides and polymyxin B. This resistance is regulated by the PhoP-PhoQ and PmrA-PmrB two-component regulatory systems. To further characterize Mg(2+) regulation in P. aeruginosa, microarray transcriptional profiling was conducted to compare wild-type P. aeruginosa grown under Mg(2+)-limited and Mg(2+)-replete conditions to isogenic phoP and pmrA mutants grown under Mg(2+)-limited conditions. Under Mg(2+)-limited conditions (0.02 mM Mg(2+)), approximately 3% of the P. aeruginosa genes were differentially expressed compared to the expression in bacteria grown under Mg(2+)-replete conditions (2 mM Mg(2+)). Only a modest subset of the Mg(2+)-regulated genes were regulated through either PhoP or PmrA. To determine which genes were directly regulated, a bioinformatic search for conserved binding motifs was combined with confirmatory reverse transcriptase PCR and gel shift promoter binding assays, and the results indicated that very few genes were directly regulated by these response regulators. It was found that in addition to the previously known oprH-phoP-phoQ operon and the pmrHFIJKLM-ugd operon, the PA0921 and PA1343 genes, encoding small basic proteins, were regulated by Mg(2+) in a PhoP-dependent manner. The number of known PmrA-regulated genes was expanded to include the PA1559-PA1560, PA4782-PA4781, and feoAB operons, in addition to the previously known PA4773-PA4775-pmrAB and pmrHFIJKLM-ugd operons.